Urban Archaeology: Hekatomnos Archaeological Site - İlayda Aykol; Hande Düzgün Bekdaş (Proceedings of the International Conference of Contemporary Affairs in Architecture and Urbanism-ICCAUA, 2025)
Cities have continuously undergone change and transformation according to needs from their establishment to the present day. Each transformation phase has left traces on the city, layered over time to form urban archaeology and cultural heritage. Since the existence of humankind, curiosity about our origins and the past leads us to these remnants. While some cities preserve identities, others, particularly archaeological and protected sites, do not always achieve this. This study aims to analyse the multi-layered structure of the Hekatomnos archaeological site in Milas, Muğla, one of the oldest cities in the Caria region, and to examine participation examples in urban archaeological sites for their applicability. It further emphasises that urban archaeological sites constitute urban identity. The research analyses the potential and productivity of this site by examining local and international examples within the Caria region, which has high productivity in urban archaeology. In this context, the effects of presenting Hekatomnos’ multi-identity as a cultural route to the public will be observed. By examining examples of integrating archaeological sites into cities, specific parameters will be established to evaluate the site. This research will fill a gap in the literature on the Hekatomnos Mausoleum.